Transmission risk of avian influenza virus along poultry supply chains in Guangdong, China. Issue 1 (July 2019) - Wu, Jian-Yong; Lau, Eric HY; Yuan, Jun; Lu, Ming-Ling; Xie, Chao-Jun; Li, Kui-Biao; Ma, Xiao-Wei; Chen, Jian-Dong; Liu, Yan-Hui; Cao, Lan; Li, Mei-Xia; Di, Biao; et al.
Highlights: Increasing circulation of avian influenza viruses along poultry supply chain. Higher circulation of avian influenza viruses translates to higher human infection risk. Strengthening control at each level of the poultry supply chain is needed. One health strategy is crucial to control transmission of avian influenza viruses. Abstract: Objectives: Avian influenza viruses (AIVs) poise significant risk to human health and the poultry industry. We evaluated the transmission risk along the poultry supply chain. Methods: During October 2015 and July 2016, four rounds of cross-sectional surveys were performed to characterize AIV spread in farms, transport vehicles, slaughterhouses, wholesale and retail live poultry markets (LPMs). Poultry cloacal and oral swabs, environmental swabs, bioaerosol samples and human sera were collected. Poultry and environmental samples were tested for AIVs by rRT-PCR, further subtyped by next generation sequencing. Previous human H9N2 infections were identified by hemagglutination inhibition and microneutralization tests. Logistic regression was fitted to compare AIV transmission risk in different settings. Results: AIVs was detected in 23.9% (424/1771) of the poultry and environmental samples. AIV detection rates in farms, transport vehicles, wholesale and retail LPMs were 4.5%, 11.1%, 30.3% and 51.2%, respectively. 5.2%, 8.3% and 12.8% of the poultry workers were seropositive in farms, wholesale and retail LPMs, respectively. The regression analysis showed that virus detection and transmission risk to human increased progressively along the poultry supply chain. Conclusions: Strengthening control measures at every level along the poultry supply chain, using a one health approach, is crucial to control AIV circulation.